Research methodology: Best practices for rigorous, credible and impactful research - Aguinis, Herman (New Delhi Sage India, 2025)
Research Methodology: Best Practices for Rigorous, Credible, and Impactful Research takes a 360-degree view of understanding and doing research, helping readers become expert researchers, reviewers, and consumers of research. Renowned author, journal editor, and researcher Herman Aguinis distills the vast body of work on methodological best practices into a singular experience. Each of the 16 chapters thoroughly explains a different aspect of methodology step by step, from choosing useful and compelling research topics to reporting results accurately and credibly.